Healthy eating: the preventive factors among Malaysians - Sharkawi, Ismawati; Mohamed, Zainal Abidin; Rezai, Golnaz (International Association of Computer Science and Information Technology, 2014)
The paper investigates the factors perceived to be important barriers to healthy eating among Malaysian adults. Data were collected from a random sample of 1719 adults throughout Malaysia via a self-administered questionnaire. Findings show that the most important perceived barriers to healthy eating were unavailability and limited choice of healthy food away from home, time constraints and busy lifestyle. Exploratory factor analysis of 22-item in perceived barriers domain revealed four factors that accounted for 76% of the variance in perceived barriers to healthy eating, namely: physical; knowledge and social; lack of time; and unavailable healthy choices. The findings of this study implied the needs for provision of wide selection and availability of healthy food to the consumers as well as promoting the nutrition and healthy eating messages effectively.